Utilizing English E-Learning: An Interesting Innovation In Modern Learning - Tanadday Lubaba; Zulfi Zumala Dwi Andriani (Darussalam English Journal (DEJ), 2025)
This study aims to The purpose of this study is to provide new innovations in English learning with electronic media at MA.M. with a qualitative approach and in-depth interview design . The subjects of the study consisted of students and English teachers of MA.M. Data collection was carried out through three main techniques: semi-structured interviews with English teachers and students of MA.M direct observation of learning activities, and collection of documents about the e-learning platform . Miles and Huberman, which includes three main stages: data reduction, data presentation, and drawing conclusions/verification. To ensure the validity and reliability of the study, data triangulation was carried out by comparing information from various sources and discussing the findings with colleagues. This study explores the improvement of teaching innovation and improving the English language skills of students of MA.M Through e-learning that adopts a digital media- based approach . In an increasingly connected world, English language skills are very important. These findings provide valuable insights for providing innovations in English learning in madrasah and similar educational institutions in the future.